Evaluating the science teacher according to the (NCATE) standard from the point of view of educational supervisors - Hanan Kazem Abd ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2020)
The current  research aims to evaluate  the science  teacher  a according  to the   From  the  viewpoint of  educational  supervisors  in             (NCATE)   criterion  Misan Governorate, this study has confirmed criterion (NCATE) and  mean the national Accreditation  council  for teacher predation  programs  and  consists of a set of key  criterion  that serve the science  teacher  and help him in  the correct evaluation  during the profession  as a science teacher is the guide and guide for the  educational process the research has prepared  a list of the main  areas of the number (8) areas from which (51) subparagraphs emerge from each of the field in their initial from prepared in the form of an open questionnaire annex(1) after reviewing the Arab and in ternational studies and projects, the criterion  (NCATE) in clouded the following fields (the profession  of the science  teacher - the personal and moral character - the educational alternatives to punishment- the educational programs- the curriculum –the teaching staff- the methods of teaching science and the educational means- the field experiences and the  scientific activities) as part of the profession of the science teacher, the  researcher used the statistical method, including the weighted media  and the percentage weights, and through that the following results were reached :                                                                                                        1-The science teacher Evaluation according  to a criterion (NCATE) was not  at the required level compared to the assumed  spoken percentage adopted by the researcher ,which (75%) according to the opinions of experts, as(33) paragraphs out of (51) paragraphs mentioned in the standard prepared for the study and its percentage (64,70%) .                                                                                       2-The field of (professional competence) was ranked first and by weigh percentage (78%) while the field of (personal and moral character), was ranked second and by percentage (78%) , and the field (methods of teacher sciences and educational means )at third rank, with a percentage of (77,66%)  followed by the field of (curriculum) at the fourth  ran with percentage (71%) while the field of (educational  al ternaries for punishment) at the fifth rank with arate of (69,66%) while the( field experiences and scientific activities) at the sixth rank and wither  a percentage (69%) while the  field (the teaching staff) at the seventh rank, with a percentage of (65%), followed by the  field of ( educational  programs) with the last rank at the rate of (62,33%) . Research recommended :                      1-prparing supervisory publication that in traduce science teachers to some  educational ideas and practices at the local  and scientific level  2- frequent visits to science teachers  by educational supervision in order to raise the efficiency and level of performance of the science teachers .To complete the study the researcher  suggested :1-conducting a similar study to evaluate science teachers according  to the comprehensive quality standards in the other academic stages.2- conducting more studies dealing with planning to develop an application (NCATE) in misan governorate .Keywords : Evaluating  , the  science teacher , according  to the (NCATE) ,  educational   supervisors .